1980
DOI: 10.1524/ract.1980.27.1.51
|View full text |Cite
|
Sign up to set email alerts
|

Solvent Extraction Studies in Miniature Centrifugal Contactors

Abstract: Solvent extraction IFuelreprocessinglCentrifugal contactors! Ruthenium jZirconiumThe contactor was also tested for application to the Civex and Thorex processes. SummaryA miniature short-residence-time centrifugal solvent extraction contactor and an eight-stage laboratory minibank of centrifugal contactors were used for testing the possibility of utilizing kinetic effects for improving the Separation of uranium from ruthenium and zirconium in the Purex process. Results of these tests showed that a small improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 3 publications
0
21
0
Order By: Relevance
“…Figure 5 shows the infrared spectra of the RuN0(N0 3 ) 3 and RUNOC13. Figure 6 shows the infrared spectra of Na 2 RuNO (N0 2 ) 4 OH • 2 H 2 Ο and RuNO (OH) 3 . The spectra show a strong absorption band in the vicinity of 1900 cm" 1 .…”
Section: Analytical Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Figure 5 shows the infrared spectra of the RuN0(N0 3 ) 3 and RUNOC13. Figure 6 shows the infrared spectra of Na 2 RuNO (N0 2 ) 4 OH • 2 H 2 Ο and RuNO (OH) 3 . The spectra show a strong absorption band in the vicinity of 1900 cm" 1 .…”
Section: Analytical Resultsmentioning
confidence: 99%
“…Nitrosylruthenium hydroxide (RuNO(OH) 3 ) was prepared by the method described by FLETCHER et al [8] and labeled with 103 Ru by neutron irradiation in the same reactor.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In many studies, high mass transfer efficiencies of uranium have been demonstrated by using miniature centrifugal contactors. [10][11][12] Kuzunetsov et al showed that the mass transfer efficiency of uranium could reach 0.95 within 2 s/stage of the mixing time. 12) In our contactor design, the mixing time was around 2 s/stage for a 10 kg-HM/h flowsheet, so it has sufficient mixing time for uranium extraction.…”
Section: Stage Efficiencies On Uranium Extraction and Stripping Sectionsmentioning
confidence: 99%